Konteks, Tema, Skemata, Memori, dan Pikiran : Mendukung Pembelajaran Bahasa Sebagai Penghela Ilmu Pengetahuan - ROKHMAWAN, TRISTAN (University of Brawijaya, 2018)
An integrative approach leads to a new point of view in interpreting learning process. This approach allows students to simultaneously mastering multiple disciplines in a an or a single learning task; linking it in the same context and theme. According to the existence of academic texts, the context supports the existence of relationships between several scientific contexts; including the content and scope of discussion related to certain fields of science. With the theme, each curricular content is able to connect in a match network to develop interdisciplinary units. This allows multiple teachers in different disciplines to join to build shared learning with integrated learning objectives; in one theme. In turn, the integrative concept allows students to think and store their learning thoughts well, connected, continuous, deep, and stronger (persisting and not easily forgotten). This means that what the student has learned is assumed to be more durable in his mind's memory. This assumption is based on the development of schemata, the storage of knowledge information in memory, and the management of the mind when integrative learning is performed.These concept can be realized in language learning. Language disciplines have unique and special functions as a carrier of knowledge and as inter-disciplinary advocates. The usefulness of these two functions is great for the functional progress of the Language disciplines. The study of language as a carrier of knowledge can be interpreted that the science of language into a vehicle that brings science to other sciences.